Uma arquitetura para a utilização de computação nas nuvens nos ambientes de computação pervasiva - Pereira, Henrique Gabriel Gularte (2012)
The modern world can be characterized by the quick proliferation of mobile devices and by the intense use of computers on our daily lives. Both pervasive computing and cloud computing have appeared as very promissing trends, but for pervasive computing to reach mainstream, many paradigm changes are needed on the current computing environments. Some of the problems found in pervasive camputing are not from a technical order, but due to a lack of standards and models to allow devices to interoperate and the problems related to the creation of low cost computing environments. Pervasive environments are marked by having sudden and frequent changes, making it necessary to think of a way to manage context information. This work aims at showing a solution that will allow the creation of pervasive computing environments using resources available in the cloud computing paradigm and taking in consideration requisites like the ability of mixing heterogenous computing devices running on the least possible amount of resources and using ontologies for context information representation and management. In this context, an architecture for the development of pervasive computing environments, an study case in a residencial cenario and an analysis of the results obtained with the proposed architecture are presented.